Agricultural Price Distortions, Poverty, and Inequality in the Philippines - Cororaton, Caesar B; Corong, Erwin; Cockburn, John (World Bank, Washington, DC, 2017)
This paper analyzes the poverty and inequality implications of removing agricultural and non-agricultural price distortions in the domestic market of the Philippines and abroad. Liberalization in the rest of the world is poverty and inequality reducing, whereas full domestic liberalization increases national poverty and inequality. Poverty declines while inequality increases marginally in the combined scenario of both global and domestic agriculture reform. Although the reduction in the national poverty headcount is small in the latter scenario, the poorest of the poor, particularly those living in the rural areas, emerge as 'winners', given their strong reliance on agricultural production and unskilled labor wages.